Optimized PCF architectures for THz detection of aquatic pathogens: Enhancing water quality monitoring - Diponkar Kundu; Nasir Uddin Badhon; A. H. M. Iftekharul Ferdous; Md. Safiul Islam; Md. Galib Hasan; Khalid Sifulla Noor; Most. Momtahina Bani (PLoS ONE, 2025)
Waterborne bacteria pose a serious hazard to human health, hence a precise detection method is required to identify them. A photonic crystal fiber sensor that takes into account the dangers of aquatic bacteria has been suggested, and its optical characteristics in the THz range have been quantitatively assessed. The PCF sensor was designed and examined as computed in Comsol Multiphysics, a program in which uses the method of “Finite Element Method” (FEM). At 3.2 THz operating frequency, the proposed sensor performs better than the others in all tested cases, with a high sensitivity of 96.78% for Vibrio cholera, 97.54% for E. coli, and 97.40% for Bacillus anthracis. It also has a very low CL of 2.095 × 10−13 dB/cm for Vibrio cholera, 4.411 × 10−11 dB/cm for E. coli, and 1.355 × 10−11 dB/cm for Bacillus anthracis. The existing architecture has the potential to produce the sensor efficiently and scalable, opening the door for commercial applications. The innovation is in the optimization of structural parameters to increase the fiber’s sensitivity to bacterial presence, thereby improving the interaction between terahertz waves and bacterial cells. It targets bacterial macromolecule absorption peaks to increase sensitivity. Localized field augmentation, which concentrates THz vibrations where bacteria interact more, may arise from optimization. By improving scattering, structural alterations can help identify bacteria by their characteristic scattering patterns. These improvements improve the sensor’s trace bacteria detection. These factors increase the sensor’s aquatic germ detection when combined. In aqueous environments, this results in a more precise and efficient detection, which could facilitate the real-time monitoring of bacterial contamination. Public health and water quality control may be significantly affected by these developments.